A New Product Growth for Model Consumer Durables - Bass, Frank M. (Management Science, 2004)
(This article originally appeared in Management Science, January 1969, Volume 15, Number 5, pp. 215–227, published by The Institute of Management Sciences.) A growth model for the timing of initial purchase of new products is developed and tested empirically against data for eleven consumer durables. The basic assumption of the model is that the timing of a consumer's initial purchase is related to the number of previous buyers. A behavioral rationale for the model is offered in terms of innovative and imitative behavior. The model yields good predictions of the sales peak and the timing of the peak when applied to historical data. A long-range forecast is developed for the sales of color television sets.